Arthroscopic resection of a loose body in the inextensible metacarpophalangeal joint of the middle finger complicated with osteoarthritis: A case report. (July 2020) - Hattori, Tetsuya; Tsujii, Masaya; Uemura, Takeshi; Sudo, Akihiro
Arthroscopic surgery is a standard technique for removal of loose bodies in large joints. By contrast, there were a few reports of arthroscopic surgery for loose bodies in small joints. We herein report a case of a 70-year-old woman with an inextensible metacarpophalangeal joint in the right middle finger due to an intra-articular loose body that developed after osteoarthritis. Surgery proceeded under vertical traction using traction tower. Two portals were developed at dorsal aspect on the metacarpophalangeal joints. The loose body was removed under arthroscopy with a small incision of both skin and sagittal band, thereby resolving clinical symptoms, including pain and limitations to metacarpophalangeal joint motion.